Surface properties tuning of exfoliated graphitic carbon nitride for multiple photocatalytic performance. (1st September 2020) - Baca, M.; Rychtowski, P.; Wróbel, R.; Mijowska, E.; Kaleńczuk, R.J.; Zielińska, B.
Graphical abstract: Highlights: Surface properties of ex. g-C3 N4 determine photocatalytic AR18 and VOP response. Positive surface charge promotes AR18 and acetaldehyde decomposition. Positively charged ex. g-C3 N4 exhibits both enhanced activity and high reusability. Abstract: Two types of exfoliated graphitic carbon nitride (GCN) with similar morphology but different surface properties were fabricated and tested as photocatalysts in acetaldehyde and dyes (Acid Red 18 and Rhodamine B) decomposition processes. Both samples were synthesized via exfoliation of the bulk GCN in the assistance of strong oxidant. Their surface modification was tuned by annealing at different temperature: 250 and 350 °C providing two samples assigned to GCN_250 and GCN_350, respectively. The samples exhibited similar thickness, lateral size, surface area and band gap energy but their photoactivity differed greatly. Exfoliated materials showed different photocatalytic activity depending on the type of dye (anionic or cationic). The Acid Red degradation by GCN_250 with positively charged surface was 1.8-times higher in respect to negatively charged GCN_350, whereas the Rhodamine B decomposition by GCN_350 was 1.4-times higher in comparison to GCN_250. Furthermore, GCN_250 exhibited superior photoactivity towards acetaldehyde decomposition in comparison with GCN_350 under visible light irradiation. This study provides knowledge on GCN surface properties in photocatalytic activity toward both water and volatile pollutant degradation.